The Pogil Learning Model and Students' Critical Thinking Improvement in History Subject - Nurul Umamah; Herlinatus Sholehah (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
Critical thinking skills (CTS) are important skills for students to filter information in the era of globalization. With the rapid growth of education, there goes the more significant challenges and advanced-technological transformation. GEN Z learners, called